2016
DOI: 10.1515/folmed-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

Landolphia owariensis Attenuates Alcohol-induced Cerebellar Neurodegeneration: Significance of Neurofilament Protein Alteration in the Purkinje Cells

Abstract: Background: Alcohol-induced cerebellar neurodegeneration is a neuroadaptation that is associated with chronic alcohol abuse. Conventional drugs have been largely unsatisfactory in preventing neurodegeneration. Yet, multimodal neuroprotective therapeutic agents have been hypothesised to have high therapeutic potential for the treatment of CNS conditions; there is yet a dilemma of how this would be achieved. Contrarily, medicinal botanicals are naturally multimodal in their mechanism of action. Aim: The eff ect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…39 In other studies, an LD50 of greater than 5,000 mg/kg was reported with the Ethanol, Methanol, Water, Hexane, and Acetone extracts of L. owariensis leaves 40 while an LD50 of greater than 3000 mg/Kg was obtained for the hydroethanolic bark extract of the plant when applied intraperitoneally. 41 It is pertinent to note that in all the previous reports in literature, there is no record of death of animals that received extracts of this plant. Another study on the aqueous leaf extract of the plant 30 indicates an LD50 of 3370 mg/Kg.…”
Section: Resultsmentioning
confidence: 98%
“…39 In other studies, an LD50 of greater than 5,000 mg/kg was reported with the Ethanol, Methanol, Water, Hexane, and Acetone extracts of L. owariensis leaves 40 while an LD50 of greater than 3000 mg/Kg was obtained for the hydroethanolic bark extract of the plant when applied intraperitoneally. 41 It is pertinent to note that in all the previous reports in literature, there is no record of death of animals that received extracts of this plant. Another study on the aqueous leaf extract of the plant 30 indicates an LD50 of 3370 mg/Kg.…”
Section: Resultsmentioning
confidence: 98%
“…After 15 days treatment, no variation was observed in albumin, total protein concentration and serum activity of ALT, AST and ALP, however, there were significant decreases in haemoglobin and bilirubin concentrations (Nwogu et al, 2008). Aqueous extract of L. owariensis bark showed no biochemical and histological effects on rats, but, extract significantly reduced the biochemical and histological neurodegeneration of cerebellar cortex and NF-IR was induced in Purkinje cells after four days treatment ( Oyinbo et al, 2016 ).…”
Section: Toxicological Profilementioning
confidence: 99%
“…The sections were dried on hot plate at 60 ºC for 2hours.The tissue were further processed by dehydrating with ascending grades of alcohol, cleared in two changes of xylene and embedded in molten paraffin wax and sectioned using rotary microtome, mounted on glass slide and stained with hematoxylin and eosin. Ultra-sections from each group were examined by light microscopy for tissue injury and neurodegenerative features such as shrinkage of the neuron, hyperchromasia, and nuclear pyknosis as exposed by heamatoxylin and eosin staining techniques following the methodology of Oyinbo et al [68]. Cortical Purkinje cells estimation was based on semi-quantitative scale described in previous study [68] was used to assess the extent of neurodegeneration in the PFC with 400× magnification.…”
Section: Hematoxylin and Eosin Stainingmentioning
confidence: 99%
“…Ultra-sections from each group were examined by light microscopy for tissue injury and neurodegenerative features such as shrinkage of the neuron, hyperchromasia, and nuclear pyknosis as exposed by heamatoxylin and eosin staining techniques following the methodology of Oyinbo et al [68]. Cortical Purkinje cells estimation was based on semi-quantitative scale described in previous study [68] was used to assess the extent of neurodegeneration in the PFC with 400× magnification.…”
Section: Hematoxylin and Eosin Stainingmentioning
confidence: 99%